2011
DOI: 10.1111/j.1399-5618.2011.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine transporter availability in unmedicated bipolar disorder

Abstract: The results of this study support the hypothesis that there are abnormalities in the dopaminergic system in BPD, and suggest that DAT availability may be related to the neuropathology of BPD. Future studies are needed to determine if DAT availability cycles with disease phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 60 publications
1
72
0
1
Order By: Relevance
“…The importance of our findings is highlighted from studies indicating that polymorphisms in the DAT gene may induce lower DAT levels in patients with BD (Anand et al, 2011;Pinsonneault et al, 2011). Lower striatal DAT levels have also been observed in people with ADHD (Fusar-Poli et al, 2012) and seasonal affective disorder (Neumeister et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The importance of our findings is highlighted from studies indicating that polymorphisms in the DAT gene may induce lower DAT levels in patients with BD (Anand et al, 2011;Pinsonneault et al, 2011). Lower striatal DAT levels have also been observed in people with ADHD (Fusar-Poli et al, 2012) and seasonal affective disorder (Neumeister et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Hence, chronic reductions of DAT expression in mice may model more aspects of BD than acute DAT inhibition alone. The etiological validity of the chronic DAT KD model is likely limited, however, by the fact that these animals express only 10% of the transporter (Zhuang et al, 2001), whereas only a B20% reduction of DAT availability is observed in euthymic BD patients (Anand et al, 2011). As yet, DAT levels in BD patients in the manic phase have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported an exception [282]). Amsterdam and Newberg [283] reported higher striatal DAT binding in the right posterior putamen and left caudate in a small number of patients with bipolar disorder; Chang and colleagues [284] reported that unmedicated euthymic subjects with bipolar disorder had significantly relatively higher whole striatal DAT binding; and Anand and colleagues [285] reported relatively lower DAT availability in the dorsal caudate nucleus (DCN) bilaterally. There is also evidence that the presence of psychosis may moderate patterns of DA receptor binding.…”
Section: Reviewmentioning
confidence: 99%